The Paradigm of Reconstructing Fazlur Rahman's Ethical-Legal Contextual Interpretation of the Qur'an: Paradigma Rekonstruksi Tafsir Kontekstual Etik-Hukum Al-Qur’an Fazlur Rahman - Nurdiansyah, Putra Pandu Dinata (Takwil: Journal of Quran and Hadith Studies, 2025)
The Qur’an contains not only spiritual and theological values but also ethical and legal principles aimed at building a just and civilized society. However, traditional approaches to interpreting legal verses of the Qur’an tend to be literalist, atomistic, and insufficiently responsive to complex social transformations. This condition highlights the urgent need for methodological renewal in interpreting the Qur’an’s ethical-legal messages to ensure their continued relevance in contemporary contexts. This study aims to examine in depth the ethical-legal interpretive paradigm of the Qur’an in the thought of Fazlur Rahman, a prominent modernist Muslim thinker who offers a moral-conceptual approach through his Double Movement Theory. The research focuses on three main aspects: (1) Fazlur Rahman’s paradigm of ethical-legal Qur’anic interpretation, (2) his critique of traditional Islamic exegesis, and (3) the implications of his ideas for the development of contemporary Islamic legal thought. This study employs a qualitative library research method using content analysis of Fazlur Rahman’s primary works and relevant secondary literature. The distinction of this study lies in its emphasis on the ethical-legal dimension of Qur’anic interpretation, a topic that has rarely been systematically explored. Its novelty lies in the integration of the Double Movement Theory within the framework of ethical-legal interpretation that is responsive to social justice values and the dynamics of modern life. The findings demonstrate that Rahman’s approach enables a reconstruction of Islamic legal hermeneutics to become more contextual, humanistic, and rooted in the Qur’an’s universal moral values. This study affirms the importance of a dynamic ethical-legal interpretive paradigm as a foundational basis for developing Islamic legal thought that remains adaptive and relevant to the challenges of the modern era.